Communio Sanctorum - Kordero, Kristian (Likhaan: The Journal of Contemporary Philippine Literature; Vol 2 (2008): Likhaan 2, 2010)
Kamatayan ni Fray Diego Ang Bisyon ni Sor Purificacion sa Impiyerno Eskapularyo Laberinto Relikwaryo Jerusalem Katiyakan